Efektivitas Metode Oral Reading Fluency (ORF) dalam Meningkatkan Kemampuan Membaca Lancar Siswa Kelas 2 SD - Merry Apriany; Chandra Chandra; Inggria Kharisma (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to evaluate the effectiveness of the Oral Reading Fluency (ORF) method in improving the fluent reading skills of second-grade elementary students. The research subjects consisted of five second-grade students who were at reading level 2. The ORF method was implemented through repeated reading, guided oral reading, and timed reading practices to enhance speed, accuracy, and expression. Data was collected through pre- and post-tests, observations, and recorded reading sessions. The results indicated significant improvements in the students' reading fluency, including increased reading speed, better word recognition, and improved comprehension. This study contributes to the understanding of literacy development in early education and highlights the importance of structured oral reading practices in enhancing reading fluency among elementary students.